Durable Response to Vemurafenib and Cobimetinib for the Treatment of BRAF-Mutated Metastatic Melanoma in Routine Clinical Practice - Álamo MC (Dove Medical Press, 2021)
Mª del Carmen Álamo,1 Sebastian Ochenduszko,2 Guillermo Crespo,3 Mónica Corral,4 Juana Oramas,5 Pilar Sancho,6 Javier Medina,7 Fernando Garicano,8 Pedro López,9 Begoña Campos Balea,10 Analia Rodríguez Garzotto,11 Eva Muñoz-Couselo12,13 1Oncology Department, Hospital Universitario Virgen Macarena, Sevilla, Spain; 2Oncology Department, Hospital Universitario Dr. Peset, Valencia, Spain; 3Oncology Department, Hospital Universitario de Burgos, Burgos, Spain; 4Oncology Department, Hospital Clínico Universitario Lozano Blesa, Zaragoza, Spain; 5Oncology Department, Hospital Universitario de Canarias, Santa Cruz de Tenerife, Spain; 6Oncology Department, Hospital Universitario Virgen del Rocío, Sevilla, Spain; 7Oncology Department, Hospital Universitario Virgen de la Salud, Toledo, Spain; 8Oncology Department, Hospital de Galdakao, Bizkaia, Spain; 9Oncology Department, Complejo Hospitalario General de Jaén, Jaén, Spain; 10Oncology Department, Hospital Lucus Augusti, Lugo, Spain; 11Medical Department and Strategy, Roche S.A, Madrid, Spain; 12Oncology Department, Hospital Universitario Vall d´Hebron, Barcelona, Spain; 13VHIO Vall d’Hebron Institute on Oncology, Barcelona, SpainCorrespondence: Eva Muñoz-CouseloOncology Department, Hospital Universitario Vall d´Hebron, Passeig de la Vall d’Hebron, 119, Barcelona, 08035, SpainEmail emunoz@vhio.netBackground: The combination of BRAF and MEK inhibitors delays the onset of resistance and provides more sustained and dramatic responses in comparison with a BRAF inhibitor in monotherapy. The objective of the study was to evaluate the effectiveness of the combination therapy with vemurafenib/cobimetinib in terms of durability, and to describe differential characteristics in patients associated to durable responses in real-world settings.Patients and Methods: Retrospective, observational, cross-sectional, multicenter study involving 41 patients with advanced melanoma harboring a BRAFV600 mutation who initiated a combination therapy with vemurafenib/cobimetinib between May 2018 and March 2019. Participants were differentiated regarding the durability of the response: durable (complete response, CR, or a partial response, PR, for at least 12 months) and non-durable (stable disease, SD, progressive disease, PD, or CR/PR < 12 months). Secondary endpoints included treatment adherence, labor productivity, anxiety/depression, and safety profile.Results: During the combination therapy, 12 patients (29.3%) had a CR, 19 a PR (46.3%), 5 showed SD (12.2%), and 5 had PD. A total of 12 patients (29.3%) were considered as achieving a durable response and 29 (70.7%) as a non-durable one. Practically all sociodemographic and clinical characteristics were similar between patients. Body mass index was the only differential factor (with higher body mass index achieving a non-durable response). The treatment adherence was 100% in patients with durable response and 66.7% in those with non-durable.Conclusion: The combination treatment with vemurafenib/cobimetinib results in an important impact on long-term survival, leading to a steady CR in one-third of the patients.Keywords: vemurafenib, cobimetinib, BRAF, metastatic melanoma, durable response, clinical practice